Production of d-lactic acid from hardwood pulp by mechanical milling followed by simultaneous saccharification and fermentation using metabolically engineered Lactobacillus plantarum. (July 2015) - Hama, Shinji; Mizuno, Shino; Kihara, Maki; Tanaka, Tsutomu; Ogino, Chiaki; Noda, Hideo; Kondo, Akihiko
Highlights: Process for high-titerd -lactic acid production from cellulosic feedstocks. Simultaneous saccharification and fermentation is suggested to improve the process. To improve saccharification of high-load pulp, high-impact pulverization is applied. A combined process for increasing the lactic acid titer above 100 g/L. Abstract: This study focused on the process development for thed -lactic acid production from cellulosic feedstocks using the Lactobacillus plantarum mutant, genetically modified to produce optically pured -lactic acid from both glucose and xylose. The simultaneous saccharification and fermentation (SSF) using delignified hardwood pulp (5–15% loads) resulted in the lactic acid titers of 55.2–84.6 g/L after 72 h and increased productivities of 1.77–2.61 g/L/h. To facilitate the enzymatic saccharification of high-load pulp at a fermentation temperature, short-term (⩽10 min) pulverization of pulp was conducted, leading to a significantly improved saccharification with the suppressed formation of formic acid by-product. The short-term milling followed by SSF resulted in a lactic acid titer of 102.3 g/L, an optical purity of 99.2%, and a yield of 0.879 g/g-sugars without fed-batch process control. Therefore, the process presented here shows promise for the production of high-titerd -lactic acid using the L. plantarum mutant.